Case study detailing precipitation and evaporation rate information for the lagoon area of a wastewater treatment plant - Paulo Stracke, Marcelo; Luft, Sandro; Cauduro Girardello, Vittor; Vanderlei dos Santos, Antônio (Seven Editora, 2023)
This article presents a detailed case study on the evaporation and water level of the lagoons at the Cooperativa Agrícola Mixta São Roque Ltda Wastewater Treatment Plant located in Salvador das Missões, Rio Grande do Sul, Brazil. The objective of the study was to quantify the evaporative losses at the Wastewater Treatment Plant and understand the behavior of the reservoirs in the region. To achieve this, information on precipitation and evaporation rates for the area of the lagoons was collected. The evaporation of water from open-air reservoirs is a factor that affects various sectors such as human water supply, energy production, livestock, agriculture, and industries. The northeastern region of Brazil, in particular, has climatic characteristics that result in approximately 70,000 open-air reservoirs due to the semi-arid climate and erratic rainfall. The Jensen-Haise method, which has proven to be efficient in arid and semi-arid regions, was used to calculate the daily evaporation rates for each month of the study period. The main factors that affect evaporation are temperature, wind, air pressure, humidity, and radiation. The results showed that the average daily value of evaporated effluent is justified and in line with the calculated values of water evaporation for the region. Additionally, data on the volume of captured rainfall and the increase in the lagoons' water level due to rainfall were presented. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-086